2010
DOI: 10.4049/jimmunol.1002129
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Infection Enhances Cross-Priming of CD8+ T Cells to Cell-Associated Antigens in a TLR7- and Type I IFN-Dependent Fashion

Abstract: The initiation of antitumor immunity relies on dendritic cells (DCs) to cross-present cell-associated tumor Ag to CD8+ T cells (TCD8+) due to a lack of costimulatory molecules on tumor cells. Innate danger signals have been demonstrated to enhance cross-priming of TCD8+ to soluble as well as virally encoded Ags; however, their effect on enhancing TCD8+ cross-priming to cell genome-encoded Ags remains unknown. Furthermore, influenza A virus (IAV) has not been shown to enhance antitumor immunity. Using influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 69 publications
2
32
0
Order By: Relevance
“…Recent studies have suggested that type I IFN enhances the CD8 + T cell response during antigen cross-presentation [17], [22], [40], [41]. To evaluate whether the temporal effect of type I IFN signaling on CD8 + T cell responses occurred in mice with impaired cross-presentation capacity, we utilized BATF3 -/- mice, which lack CD8-α and CD103 + dendritic cells [18], [42].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that type I IFN enhances the CD8 + T cell response during antigen cross-presentation [17], [22], [40], [41]. To evaluate whether the temporal effect of type I IFN signaling on CD8 + T cell responses occurred in mice with impaired cross-presentation capacity, we utilized BATF3 -/- mice, which lack CD8-α and CD103 + dendritic cells [18], [42].…”
Section: Resultsmentioning
confidence: 99%
“…Type I IFN stimulates effector T cells, as well as DCs, promoting their maturation and survival and the enhancement of DC crosspresentation (35)(36)(37)45). For example, the coinjection of a high dose of soluble IFN-a/b plus Ag (35) or the injection of DCtargeted DEC205-binding Ag in combination with the IFN-a/b inducer polyinosinic:polycytidylic acid (36) stimulates T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…Hemagglutination inhibition (HI) assay serum samples were treated with receptor-destroying enzyme (RDE; Denka Seiken Co., Tokyo, Japan) overnight at 37°C, followed by heat inactivation (56°C for 30 min). Serially diluted sera in V-bottom 96-well plates were tested in duplicate for their ability to inhibit the agglutination of 0.5% turkey red blood cells by 4 HAU of PR8 or Cal/08 virus in a standard HI assay as described previously (60). Numbers were converted to a log 2 scale to determine statistical significance.…”
Section: Methodsmentioning
confidence: 99%